Effectiveness of Educational Interventions on Student Knowledge of First Aid for Sports Injuries - Perangin-angin, Indra Hizkia; Tumanggor, Lili Suryani; Tondang, Gryttha (Madago Nursing Journal, 2025)
Background: This study evaluated the effectiveness of structured educational interventions in improving students’ knowledge of first aid for sports-related injuries. Adolescent injuries remain a significant school-based health concern, often exacerbated by knowledge gaps. This study addressed a gap in the literature by testing a multi-session intervention using a controlled experimental design to provide empirical evidence on its impact. Methods: A quasi-experimental pre-test–post-test control group design was conducted at SMA RK Deli Murni Diski, Medan, Indonesia, over three months (October–December 2024). Seventy students participated (36 intervention, 34 control). Data were collected using a validated 25-item questionnaire (Cronbach’s α = 0.87) administered before and after the intervention. Ethical approval and informed consent were obtained. Results: The intervention group’s mean score rose significantly from 13.62 ± 2.10 to 24.29 ± 2.39 (p < 0.001), while the control group’s increase from 13.71 ± 2.57 to 16.38 ± 3.33 was not significant. The percentage of students with “good” knowledge increased from 8.3% to 86.1% in the intervention group. The effect size was large (Cohen’s d = 4.80), supporting the intervention’s impact on knowledge retention. Conclusion: Structured school-based first aid education significantly enhances students’ readiness to manage sports injuries. Integrating such training into school curricula can promote youth health literacy and emergency preparedness. Future studies should assess long-term skill retention and behavioral outcomes.